Girls crash too: trends in single vehicle crash rates in young and adult, male and female drivers. Issue 3 (20th October 2016) - Jones, Sarah J
Abstract : Young adult drivers (YADs) are over-represented in crashes mainly because of their age and inexperience. Studying single vehicle crashes by age and sex may identify new approaches to intervention. In 2014, male YAD (17–19 years) crash casualty rates were 11.4 times higher than older drivers (30–59 years), compared with 17.6 times higher in 2005, and 1.9 times female YAD, compared with 2.5 times higher in 2005. Crash casualty rates involving male and female YADs are declining. Action is needed to address YAD crash casualties involving both males and females. Graduated driver licensing is a universal approach that has the potential to do this.